Pengaruh Komisaris Independen dan Karakteristik Komisaris Audit Terhadap Internet Financial Reporting Disclosure - Rudi Zulfikar (Universitas Muhammadiyah Metro, 2019)
This study aimed to analyze the influence of the proportion of Independent Commissioner and the characteristics Audit Committee to internet financial reporting disclosure. Proportion of Independent Commissioner measured by the ratio of owned Independent Commissioner to Board of Commissioners. Characteristics of the Audit Committee is proxied by the size, Audit Committee’s meeting frequency, the Audit Committee expertise in accounting / financial, and the independent parties of the Audit Committee’s proportion. Internet financial reporting disclosure is measured by the disclosure items required under the Bank Indonesia Regulation No. 7/50/PBI/2005. The sample in this research were 90 companies, and samples used in this study were banking companies listed in Bank Indonesia during the years 2011-2014. Statistical method used is multiple regression analysis. Based on the test results show that the proportion of independent commissioner, had no effect to internet fianncial reporting disclosure. And then, the characteristics of an audit committee comprised of several proxies which are the size of the Audit Committee, Audit Committee’s meeting frequency, Audit Committee expertise in financial / accounting, and the independent parties of the Audit Committee had a positive and significant effect to the internet financial reporting disclosure. Size as control variabel had a positive and significant effect to the internet financial reporting disclosure.